Tortopus Needham & Murphy and Tortopsis Molineri (Ephemeroptera, Polymitarcyidae) new species and new records from Brazil and Ecuador - Carlos Molineri; Frederico F. Salles; Rafael Boldrini (Revista Brasileira de Entomologia, 2012)
Tortopus Needham & Murphy, 1924 and Tortopsis Molineri, 2010 with six and 10 species, respectively, are sister genera distributed in the Neartic and Neotropical regions. In spite that most species are known from the tropics of South America, only one species of each of these groups have been recorded from Brazil. Here we present distributional data expanding greatly the range of these groups including three new country records for Brazil: Tortopus igaranus Needham & Murphy, 1924, Tortopsis limoncocha Molineri, 2010 and Tortopsis spatula Molineri, 2010. We describe a distinct new species, Tortopus ipixuna sp. nov., from male imagos, that present a unique subrectangular pedestal. Additionally we redescribe the male imago of Tortopus harrisi Traver, 1950 (previously known only from the holotype), and we give the first records for Tortopsis canum Gonçalves, Da-Silva & Nessimian, 2011 from Espírito Santo and for Tortopsis spatula from Ecuador. Some variations in morphological structures of these species are also described, illustrated and discussed.